China's 13th Five year Plan: Its Implications for Thailand - พานิชสาส์น, อักษรศรี (ASIA PARIDARSANA, 2017)
This paper reviews China’s 13th Five Year Plan as a blueprint to guide the country's economic and social development from 2016 through 2020 and analyzes its economic implications for Thailand. Under this 13th Five Year Plan, the Chinese government sets out the goals and targets for China’s development in the next five year in order to intensify its efforts to reform towards a consumer-driven economy and to maintain an average annual GDP growth rate of 6.5% until 2020. This growth rate, coupled with a smooth transition to a growth model to be driven by consumption and services, will hopefully guide the economy into its “new normal” period. Strategically important, China’s 13th Five Year Plan is an important part of President Xi Jinping’s Chinese Dream (Zhongguo Meng), which is aimed to prepare for the celebration of the centennial anniversary of the founding of the Communist Party of China (CPC) and at the same time be meet the deadline in 2020 for realizing China's goal of becoming “a moderately prosperous society in all respects” or “Xiao Kang” in Chinese. Therefore, this trend will have a significant implication for Thailand and the region, given the size and global influence of the China’s economy. Given its great potential for an enlarged Chinese middle class, China’s 13th Five Year Plan will importantly have significant business implications, not only for China, but also for Thailand. Thus, this paper analyzes China’s future economic potentials and benefits for Thailand and makes some recommendations for the Thai government and the Thai private sector in the final part of this article.